2020
DOI: 10.3390/sym12061056
|View full text |Cite
|
Sign up to set email alerts
|

Cloud Detection for Satellite Imagery Using Attention-Based U-Net Convolutional Neural Network

Abstract: Cloud detection is an important and difficult task in the pre-processing of satellite remote sensing data. The results of traditional cloud detection methods are often unsatisfactory in complex environments or the presence of various noise disturbances. With the rapid development of artificial intelligence technology, deep learning methods have achieved great success in many fields such as image processing, speech recognition, autonomous driving, etc. This study proposes a deep learning model suitable for clou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(26 citation statements)
references
References 50 publications
0
26
0
Order By: Relevance
“…In addition, refinements were done on small patch masks rather than large masks of the entire Landsat 8 scenes. In another work, the authors of Cloud-AttU [51] employed a UNet model that is enriched with a specific attention module in its skip connections. Multiple attention modules enabled the model to learn proper features by paying attention to the most relevant locations in input training images or feature maps.…”
Section: Related Workmentioning
confidence: 99%
“…In addition, refinements were done on small patch masks rather than large masks of the entire Landsat 8 scenes. In another work, the authors of Cloud-AttU [51] employed a UNet model that is enriched with a specific attention module in its skip connections. Multiple attention modules enabled the model to learn proper features by paying attention to the most relevant locations in input training images or feature maps.…”
Section: Related Workmentioning
confidence: 99%
“…Studies have demonstrated the potential for CNNs to enhance cloud detection using high-resolution (<100 m) LEO satellites such as Landsat-8. [40][41][42][43][44] One study had overall cloud detection accuracy of 97.05% from Landsat-8 images and provided examples of successful identification of clouds over snow and ice. 42 Some CNNs also distinguish between optically thin and thick clouds, 40,41 which would allow for special treatment of areas where the surface is visible.…”
Section: Optically Thin Cloudsmentioning
confidence: 99%
“…Single-scene algorithms can utilize the spatial context through deep learning approaches. Deep cloud detection largely relies on the U-net architecture and has been shown to outperform the Fmask algorithm, [25,117,102]. The deep learning approach requires a large annotated data set.…”
Section: B2 Detecting Clouds In Satellite Imagesmentioning
confidence: 99%